The Application of Push Button Switch as Inverse Kinematics Input on Adaptive Walking Method for Hexapod Robot - Pola Risma; Muhammad Bagaskara; Nyayu Husni Latifah; Masayu Anisah; Adella Rialita (Universitas Sriwijaya, 2020)
Any kinds of natural disaster are undesirable. Loss and damage are the most experienced as they come. Property and people have to be relieved, and it's not an easy matter. Among the deaths caused by buildings, some may still be alive and need helps as soon as possible, but this is too risky for the rescue team since the location is still in dangerous level. Therefore, we created the detector hexapod robot to replace the tasks of the rescue teams in searching for the victims of the disasters, so there are no more victims from the rescue team. The hexapod robot is a six-legged robot which shapes and runs like a spider. This research focuses on the analysis of the push button switch as a robotic foot control input. This is because walking technique is an effective major factor in navigation of robots. A good method is required to maintain the height of the robot's foot while it is walking. So to solve this, the push button switch application is used along with the inverse kinematics calculations on each routine program in adjusting the position of the end effector on the floor surface. In shifting, the navigation runs well without any failure if the position of the foot does not touch the floor. The test is done in 2 steps, comparing the inverse kinematics calculations with x and y inputs which are applied to the robot program code then comparing the travel time condition by using push button switch and without push button switch. The result of robot in this study can be re-developed in the future, using servos with greater torque and better control input than push button switch.